Prevalence of operative complications in obstetric and gynecological surgeries requiring interventions by a general surgeon and their associated risk factors: A retrospective study in a tertiary care hospital in Vindhya region - Singh, Saddam; Singh, Ashish Pratap; Chouhan, Anil; Patidar, Ajay (Asian Journal of Medical Sciences, 2022)
Background: Surgical complications can occur in any surgery despite the best possible efforts, thereby affecting the prognosis. Gynecological and obstetric surgeries also result in some complications which require interventions by a general surgeon. These complications can be either causing hemodynamic instability, urinary tract injury, gastrointestinal tract injury, or infections. Aims and Objectives: The present study designed to identify and classify the various complication in obstetric and gynecological surgeries requiring interventions by a general surgeon and to correlate the various risk factors that predispose to these complications. Materials and Methods: The present retrospective study was conducted in the Department of Obstetrics and Gynecology and Department of Surgery, Shyam Shah Medical College and associated hospitals, Rewa, M.P., for 6 months from January 2021 to June 2021. Gynecological and obstetric surgeries resulting in complications requiring surgical intervention were identified and classified based on patients’ demographic characteristics, comorbidities, and type of complications. Results: A total of 1356 cases undergoing an obstetrical or gynecological procedure in the department of obstetrics and gynecology were studied. About 2.14% of the patients had some kind of intraoperative or post-operative complications, which required intervention by a general surgeon. The mean age of females having complications was 37.17±3.71 years. Overall the most common complication was surgical site infection with 48% of the total cases. Conclusion: In this present study, the incidence of surgical complications in obstetrical and gynecological surgeries, which is associated with higher morbidity postoperatively. These complications can be prevented by proper vigilance and surgical technique in high-risk patients.